An MPPT micro solar energy harvester for wireless sensor networks - Senivasan, S. (Institute of Electrical and Electronics Engineers Inc., 2017)
Wireless Sensor Networks (WSN) have been successfully deployed in many applications areas including agriculture, transportation, industrial and healthcare. However, they are generally powered by batteries and constrained by its finite energy resource. Therefore, energy harvesting has been proposed to ensure a longer lifespan for the WSNs. Solar energy harvesting is considered the most effective for WSN that are placed outdoor, because it has the highest power density. In this paper, solar harvesting using a low-power IC based Maximum Power Point Tracker (MPPT) is designed to provide better efficiency from solar panel. The solar harvester also includes rechargeable batteries that provides energy during the absence of sunlight and a DC-DC converter to regulate the voltage to the WSN mote. Results from the hardware prototype testing show that the MPPT enabled solar harvester can provide not only the required energy to sustain the operation of the mote, but also an increase in efficiency. © 2017 IEEE.